Avaliação quali-quantitativa de mapas conceituais produzidos por alunos de uma turma de Licenciatura em Química - MACIEL, Mayra Mylla Pereira (2022)
In chemistry teaching, it is possible to highlight the difficulties that students have in connecting the theories developed in the classroom with the reality around them. In this case, it is necessary to use different learning performance strategies. Meaningful learning becomes effective when there are relationships between new concepts and previous knowledge stored in cognitive structures. In this context, concept maps can be used as tools for the construction of hierarchy and knowledge. A tool to identify students' prior knowledge. A concept map is a diagram that represents the relationship between concepts contained in a propositional hierarchy. The tool is an active learning style. Concept maps have been increasingly studied and explored in the educational field for their potential as a methodological tool in order to achieve an effective teaching-learning process. In view of this, an undergraduate class of the Degree in Chemistry was submitted to qualitative-quantitative research. This class participated in a process of production of concept maps about the content of Chemical Bonds, being a map built without theoretical foundation and another built after an expository class of both the content and the process of elaboration of concept maps, to evaluate the differences among these. The data were collected and analyzed in a quantitative and qualitative way, and it was possible to observe a considerable improvement in the maps prepared after classes. The methodology was considered effective and satisfactory in the evaluation scope, proving to be an important subsidy for the teaching of chemistry.